Aplikasi Pengarsipan Surat Masuk dan Surat Keluar Berbasis Web pada SMP Negeri 32 Pekanbaru - Yulisman, Yulisman; Wahyuni, Refni; Irawan, Yuda (Program Studi Teknik Informatika Universitas Pamulang, 2020)
Archiving incoming and outgoing mail is very important in an organization, especially for institutions such as SMP Negeri 32 Pekanbaru. The filing of letters at SMP Negeri 32 Pekanbaru is still done by writing incoming and outgoing letters on the agenda book and storing letters in filing cabinets, making it difficult to find old letter archives and often losing letters. The purpose of this research is to find the right solution so that the archiving of incoming and outgoing mail at SMP Negeri 32 Pekanbaru is more effective and efficient by making an application for archiving incoming and outgoing mail. The method used in this research is the system development model method, namely the Waterfall Model. The application design and analysis model uses the UML (Unified Modeling Language) model which is an object-oriented language or OOP (Object Oriented Programming). Application development and development uses a static programming language, namely PHP (Hypertext Pre-processor) and MySQL as application database. The results of the research on the making of incoming and outgoing mail archiving applications are very helpful and easier for SMP Negeri 32 Pekanbaru in filing incoming and outgoing mail, especially the Administration (School Administration) section because letter archiving is already stored in the database. The conclusion is that the application is very easy and helpful in archiving incoming mail and this letter is evident from the user's assessment of the application with a value of 92% more effective and efficient.